Ecological states : politics of science and nature in urbanizing China - Rodenbiker, Jesse, 1983- (Environments of East Asia, 2023)
"This book analyzes how science-based nature protection campaigns are transforming society and the environment through extensive fieldwork in China's southwestern cities. Furthermore, it examines the role of ecology in constituting state power and social inequality"--